Herméneutique des gestes et maîtrise des passions : quelques remarques sur la sémiotique du corps dans la littérature sur l’ambassadeur en Italie et en France au début de l’époque moderne - Dante Fedele (Laboratoire Italien)
This paper examines the ethical and political issues of gesture in Early Modern diplomacy, based on a discussion of the problems raised by the interpretation of the gestures that appear on the surface of the ambassador and his counterpart’s body. Our aim is to know how this semiotics of the body became a matter of debate in the literature on the ambassador that spread throughout Europe from the late Middle Ages onwards. The paper focuses in particular on Italian and French works. Some writings from diplomatic practice are also used to provide examples and a complement to our analysis.